Impact of an Educational Program on Quality of Life among Patients Undergoing Hemodialysis in Akre/ Iraqi Kurdistan Region - Zikri Mahmood Mirza (Erbil Journal of Nursing and Midwifery)
Background and Objective: Chronic kidney diseases is an international public health issue, and it has a rising extent, occurrence and significant treatment expenditures. The guidance is a crucial step in raising the standard of dialysis care and improving the results of quality of life for end- stage renal disease patients. Therefore, the study's objectives were to establish, implement, and evaluate the impact of the educational program on hemodialysis patients' quality of life at the study site.